Learning Groups: refining technologies and social processes for climate resilient agriculture - Méndez, Kharla Vianca S.; Vidallo, Rene R.; Rosimo, Magnolia M.; Angeles, Darlyn R; Bernardo, Eisen Bernard; Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Impacts of climate change are location-specific, hence the need to develop targeted solutions and strategies. Local government units, in partnership with the International Institute of Rural Reconstruction, established farmer learning groups which are platforms for knowledge generation and sharing on climate change action-research. The project was implemented in learning communities in Guinayangan, Quezon and Ivisan, Capiz, Philippines. Facilitating learning groups involved social learning methodological processes: vulnerability assessments, setting of learning agenda, participatory action research implementation, community mobilizing and knowledge sharing.